2023
DOI: 10.3390/su15043444
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Simulation of Blood Cells Separation in a Polymeric Serpentine Microchannel under Dielectrophoresis Effect

Abstract: The current work presents a novel microfluidic approach, allowing a full separation of blood cells. The approach relies on using a polydimethylsiloxane serpentine microchannel equipped with a series of electrodes, providing two separation zones. The proposed design exploits the unique configuration of the channel along with the inherent difference in dielectric properties of the three kinds of blood cells to achieve a size-based sorting. The platelets (PLTs) are subjected to a larger dielectrophoretic force th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Their results showed that circulating tumor cells were effectively isolated with semicircular electrodes. Ayash et al [15] proposed a serpentine microchannel for the separation of RBCS and WBCS, comprising a cell inlet, a buffer inlet, and two cell outlets. Simulation results showed that by altering the flow rate ratios of the two inlets, a separation efficiency of 100% was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that circulating tumor cells were effectively isolated with semicircular electrodes. Ayash et al [15] proposed a serpentine microchannel for the separation of RBCS and WBCS, comprising a cell inlet, a buffer inlet, and two cell outlets. Simulation results showed that by altering the flow rate ratios of the two inlets, a separation efficiency of 100% was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the simulation of polymerization reactions is viewed as a unique challenge, since they are complicated and need a combination of different computational methodologies. The urethane reaction (whether formation of rigid or flexible foam) is the best example of complicated polymerization reactions, and it is important to be understood, as it has many applications [6][7][8].…”
Section: Introductionmentioning
confidence: 99%